Effect of total and differential somatic cell count on yield, composition and predicted coagulation properties from individual dairy cows. (13th March 2022) - Mariani, Elena; Cipolat‐Gotet, Claudio; Stefanon, Bruno; Zecconi, Alfonso; Stocco, Giorgia; Sandri, Misa; Ablondi, Michela; Mountricha, Maria; Summer, Andrea
Abstract : This study aimed to investigate the effect of interaction between total (SCC) and differential somatic cell count (DSCC) on milk yield, composition and coagulation traits from individual dairy cows. A total of 159 224 test‐day records (daily milk yield, composition and coagulation traits) have been collected during a period of 14 months from 12 849 Holstein‐Friesian and 9275 Simmental cows farmed in 223 herds. The interaction between somatic cell traits was highly significant for almost all the evaluated traits. This study showed that the combined use of SCC and DSCC can be employed for assessing the performances of dairy cows and for monitoring the improvement of milk quality. Abstract : Impact of different levels of total and differential somatic cells on milk quality and coagulation properties.